Le français hors de France à l’épreuve de l’italien dans le Nuovo Garzanti di Francese de 1992 - Barsi, Monica (Ponti/Ponts, 2021)
This paper focuses on the treatment of words used in French-speaking countries outside France as recorded in the Nuovo Garzanti di Francese, a French-Italian bilingual dictionary published in Milan in 1992 by Garzanti within the collection Grandi Opere. In the history of lexicography, this recording procedure is significant because it coincides with Bernard Quemada’s idea of a dictionary of the francophonie outside France expressed in those years. Among the preliminary studies, Gabrielle Quemada’s report written on behalf of the Publisher enables us to appreciate the planning level of this important reference book. It appears clearly that the inclusion of geographic variety was to be one of the hallmarks of the dictionary. In fact, the dictionary records more than one hundred words employed by French speakers living in Switzerland, Belgium, Quebec and French-speaking Africa. In a period when geographical variety still needed to be translated without using online resources, NGF offers an example of fine adaptations and effective equivalents of French words coming from less known realities.